Strong Short‐Range Cooperativity in Hydrogen‐Bond Chains. Issue 26 (1st June 2017) - Dominelli‐Whiteley, Nicholas; Brown, James J.; Muchowska, Kamila B.; Mati, Ioulia K.; Adam, Catherine; Hubbard, Thomas A.; Elmi, Alex; Brown, Alisdair J.; Bell, Ian A. W.; Cockroft, Scott L.
Abstract: Chains of hydrogen bonds such as those found in water and proteins are often presumed to be more stable than the sum of the individual H bonds. However, the energetics of cooperativity are complicated by solvent effects and the dynamics of intermolecular interactions, meaning that information on cooperativity typically is derived from theory or indirect structural data. Herein, we present direct measurements of energetic cooperativity in an experimental system in which the geometry and the number of H bonds in a chain were systematically controlled. Strikingly, we found that adding a second H‐bond donor to form a chain can almost double the strength of the terminal H bond, while further extensions have little effect. The experimental observations add weight to computations which have suggested that strong, but short‐range cooperative effects may occur in H‐bond chains. Abstract : Unchained : Experiments and calculations show that the energies (Δ G ) of hydrogen bonds can double upon formation of a chain of hydrogen bonds, but further extension of the chain results in a surprisingly negligible additional cooperative effect (A=H‐bond acceptor).